Increased Risk of Temporomandibular Joint Disorder in Osteoporosis Patients: A Longitudinal Study - Kim, So Young; Yoo, Dae Myoung; Kwon, Mi Jung; Kim, Ji Hee; Kim, Joo-Hee; Byun, Soo-Hwan; Park, Bumjung; Lee, Hyo-Jeong; Choi, Hyo Geun (Frontiers in Endocrinology, 2022)
Background: The objective of this study was to investigate the risk of temporomandibular joint disorder (TMD) in patients with osteoporosis. Methods: Data from the Korean National Health Insurance Service-Health Screening Cohort from 2002 to 2015 were collected. Participants ≥ 40 years old were enrolled, and the history of osteoporosis was evaluated. The 62,328 osteoporosis patients were matched for age, sex, income, and region of residence with 62,328 control participants. The occurrence of TMD was assessed in both the osteoporosis and control groups during the follow-up period. Stratified Cox proportional hazard analyses for TMD were conducted for the osteoporosis and control groups. The hazard ratios (HRs) of osteoporosis for TMD were further analyzed by age and sex subgroups. Results: A total of 1.2% (725/61,320) of the osteoporosis patients and 0.6% (339/61,320) of the control participants had TMD (P<0.001). Osteoporosis was associated with an elevated HR of TMD (adjusted HR=1.96, 95% CI=1.72–2.23, P<0.001). Among the age and sex subgroups, the < 60-year-old male group demonstrated an adjusted HR of osteoporosis for TMD as high as 4.47 (95% CI=1.17–17.12, P=0.029). Other age and sex subgroups also showed a higher HR for TMD associated with osteoporosis (adjusted HR=2.30, 95% CI=1.90–2.78, P<0.001 for the ≥ 60-year-old female group). Conclusion: Osteoporosis was related to a higher risk of TMD in the adult population. A prominent association of osteoporosis with TMD was noted in middle-aged men and older women.